Cyberpreneurship Research Trends and Insights from 1999 to 2023 - Aprillia, Ariesya; Kuswoyo, Chandra; Kristiawan, Allen; Sunarjo, Richard Andre; Awhina, Ridan Ahsani Te (Pandawan, 2024)
Cyberpreneurship, as a subset of entrepreneurship, is an emerging field focusing on the use of digital platforms and technologies in business. This study aims to analyze the development and trends in cyberpreneurship research over the past 17 years (1999-2023). The objective s to map the landscape of cyberpreneurship publications, identifying key countries, institutions, journals, authors, and keywords that dominate the field. Using the Dimensions citation indexing database, a bibliometric analysis was conducted, employing VOSviewer for visualizing the relationships among authors, institutions, and keywords. Data was examined based on publication pairs, co-authorship networks, and keyword co-occurrence. The analysis shows that Malaysia leads in cyberpreneurship research, with Multimedia University as the most influential institution, and Education and Training as the most cited journal. The research also highlights a significant growth in cyberpreneurship studies, especially in the last few years, indicating its increasing importance post-COVID-19. The findings suggest that cyberpreneurship is still in its early stages, with substantial potential for future research, particularly in the application of artificial intelligence and digital business models. Further exploration is recommended, especially in countries like Indonesia, where digital entrepreneurship is rapidly evolving.